Soil-transmitted helminth infections. Issue 10117 (20th January 2018) - Jourdan, Peter Mark; Lamberton, Poppy H L; Fenwick, Alan; Addiss, David G
Summary: More than a quarter of the world's population is at risk of infection with the soil-transmitted helminths Ascaris lumbricoides, hookworm ( Ancylostoma duodenale and Necator americanus ), Trichuris trichiura, and Strongyloides stercoralis . Infected children and adults present with a range of medical and surgical conditions, and clinicians should consider the possibility of infection in individuals living in, or returning from, endemic regions. Although safe and effective drugs are donated free to endemic countries, only half of at-risk children received treatment in 2016. This Seminar describes the epidemiology, lifecycles, pathophysiology, clinical diagnosis, management, and public health control of soil-transmitted helminths. Previous work has questioned the effect of population-level deworming; however, it remains beyond doubt that treatment reduces the severe consequences of soil-transmitted helminthiasis. We highlight the need for refined diagnostic tools and effective control options to scale up public health interventions and improve clinical detection and management of these infections.